PERFORMANCE TEST OF MAGNETIC RESONANCE IMAGING MACHINE 0,35 TESLA AT KASIH IBU HOSPITAL SABA - Purnama Dewi, Gusti Agung Putu Adhinta; Prasetya, I Made Lana; Sugiantara, I Wayan Ariec (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Background: This research on the performance testing of the Magnetic Resonance Imaging (MRI) machine was conducted using performance tests on three different parameters at Kasih Ibu Hospital Saba. This research aims to determine the performance of the MRI machine at Kasih Ibu Hospital Saba in Bali Province and establish baseline data for future testing. Method: This type of research is quantitative and uses a survey approach. The tools and materials used in this study are a 0.35 Tesla MRI machine, an ACR phantom, and a head coil. Data were collected by conducting nine MRI performance testing procedures using the ACR (2015) guidelines and then analyzed using international standards issued by ACR (2015). Result: In the visual checklist testing, all observed parameters were over 30 days and functioned well, For the Artifact Evaluation test, the author evaluated all scanned images and found no artifacts. The author analyzed the measurements from the first slice of T1W and T2W images for the Slice Thickness Accuracy test. The measurement results for the T1W image were 4.6mm, and for the T2W image, they were 5.57mm. The Slice Thickness Accuracy testing standard set by ACR in 2015 is 5mm ± 0.7mm. Therefore, based on the measurement results from the T1W and T2W images, the MRI machine at Kasih Ibu Saba Hospital meets the established international standards. Conclusion: Based on the results of the visual checklist test, the following results were obtained: all parameters on the visual checklist functioned well during the 30-day observation. Meanwhile, the two tests conducted with the phantom on the MRI machine at Kasih Ibu Hospital Saba the following results are: the artifact evaluation test and the slice thickness accuracy test met the international standards set by ACR in 2015.